Draft Tenth Plan 2002-2007 & Draft Annual Plan 2002-2003 Part-1 - Planning Commission (Planning Commission, 2002)
The Tenth Five Year Plan (2002-07) is being prepared against the backdrop of new Millennium and expectations of higher standard living arising among the people of the country in the context of reforms. While encouraging progress could be achieved in last decade on basic indicators such as reducing percentage of population below poverty line, declining trend of growth of population, significant increase of percentage of literacy, new source of strength on software and IT related services, yet a number of areas e.g. slowing down of world economy, slow generation of employment opportunities, stagnating position of infant mortality rate, a large gap in providing household power connection and water connection, degradation of forests, over exploitation of ground water etc. have remained as cause for concern.
Planning (P&C) Department Government Of Tripura